Penerapan Prinsip Ekonomi Manajerial terhadap Pola Pengeluaran Bulanan Mahasiswa - Zivo Carter Neyland; Maharani Tulangouw; Rexy Andalangi Maatuil; Chindy Gaharpung; Frisilia Ahiki (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2026)
Personal financial management is an essential skill for university students, especially as they must balance limited income with increasing academic and social needs. Although they have studied Managerial Economics concepts such as efficiency, cost–benefit analysis, and rational decision-making, the practical application of these theories in daily life is often not fully optimal. This study aims to analyze how students manage their monthly expenses, evaluate the extent to which managerial economics principles are applied, and identify factors that influence their consumption behavior. This research uses a qualitative method through in-depth interviews with ten students in their 5th and 7th semesters. Thematic analysis was conducted to identify patterns in financial management, spending priorities, cost–benefit considerations, as well as the influence of social factors and financial literacy. The findings indicate that some students have implemented managerial economics principles, such as budgeting and evaluating benefits and costs before making purchases. Students who consistently record their expenses tend to be more efficient and able to distinguish between needs and wants. However, others still exhibit consumptive and impulsive behavior, with minimal financial tracking, leading to imbalances between income and expenses. These results also illustrate the presence of bounded rationality influenced by emotions, social environment, and limited information. The study concludes that improving financial literacy and strengthening the integration of managerial economics theory with daily financial practices is essential to support better financial decision-making among students.